Characteristics Knowledge Law and Method Legal Research - Restika Ndruru; Yasmirah Mandasari Saragih; Tamaulina Br. Sembiring (Green Social: International Journal of Law and Civil Affairs, 2025)
Legal issues are increasingly developing, this is in line with the development of information technology. A legal research method is needed as an instrument to explain and examine legal issues that are increasingly developing. The results show that there are 3 (three) types of legal research methods, namely normative legal research methods, empirical legal research methods, and socio-legal research methods and discuss research from its nature, form, and purpose. And discuss the characteristics of legal science and legal research methods. The research method is qualitative by using the type of literature study (journal analysis, paper analysis, or other media). This research method is a literature study, namely looking for various articles that are relevant and quoting from various sources.